Tanggungjawab Pejabat Pembuat Akta Tanah atas Pembatalan Akta Hibah: Studi Putusan Nomor : 3750/Pdt.G/2021/PA.JS - Melvina; Gunadi, Ariawan (Universitas Serang Raya, 2023)
The land deed registrar has the authority to make authentic acts concerning certain legal acts or rights to land as regulated in Government Regulations Number 24 of 2016 on the regulations of the land deed department. The one where there is a fact on the ground that many incidents of cancellation of grants are assessed to not give a sense of justice for the parties, because of the lack of responsibility of the land deed registrar both in terms of form and material as the official authority to make grants rights on the land. The purpose of this research is to know and analyze the responsibility of the land registry officer for the cancellation of the grant act and to know the legal force of the subsidy act made by the land registry officer. This study uses a type of normative legal research. The results of the research showed that the grant acts made by the authorized land registrar officials are expected to qualify for the grant, and in terms of form and material, when there are errors committed by the land registrar officer, then the land registrar officer can be charged with administrative, civil, and criminal liability.